“THE NATURAL DRAMA” OF LESYA UKRAINKA - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The great poet of the Ukraine, a woman with a tragic fate, Lesya Ukrainka entered the consciousness of generations as a symbol of independence and control. By the strong spirit of the cohort attach it made life and creative achievement. As a thirst for life, a thirst for creativity, a thirst for knowledge and work Lesya Ukrainka wee fire was just best, only courageous, all the best for the people that came down to fight against social and national oppression. Life bedeviled poet deeply and relentlessly. Seriously ill body, poet-fighter was mighty soul, she lived a heroic life, ideas of heroism itself was unconquered tribes characters.